Anatomy & physiology : the unity of form and function - Saladin, Kenneth S.; Gan, Christina A.; Cushman, Heather N. (New York, NY : McGraw-Hill Education, 2021)
"Anatomy & Physiology: The Unity of Form and Function tells a story comprised of many layers, including core science, clinical applications, the history of medicine, and evolution of the human body. Saladin combines this humanistic perspective on anatomy and physiology with vibrant photos and art to convey the beauty and excitement of the subject. To help students manage the tremendous amount of information in this introductory course, the narrative is broken into short segments, each framed by expected learning outcomes and self-testing review questions" -- Provided by publisher.
Organization of the body -- Support and movement -- Internal coordination and control -- Circulation and defense -- Intake and output -- Reproduction and the life cycle.
Includes index.
Keywords: Human physiology -- Textbooks; Human anatomy -- Textbooks; Anatomy; Physiological Phenomena; Human anatomy; Human physiology; Textbooks; Textbooks